A systematic review on visual scanning behaviour in hemianopia considering task specificity, performance improvement, spontaneous and training-induced adaptations. - Postuma, Eva M. J. L.; Heutink, Joost; Tol, Sarah; Jansen, Josephien L.; Koopman, Jan; Cornelissen, Frans W.; de Haan, Gera A. (Disability & Rehabilitation, 2024)
People with homonymous hemianopia (HH) benefit from applying compensatory scanning behaviour that limits the consequences of HH in a specific task. The aim of the study is to (i) review the current literature on task-specific scanning behaviour that improves performance and (ii) identify differences between this performance-enhancing scanning behaviour and scanning behaviour that is spontaneously adopted or acquired through training. The databases PsycInfo, Medline, and Web of Science were searched for articles on scanning behaviour in people with HH. The final sample contained 60 articles, reporting on three main tasks, i.e., search (N = 17), reading (N = 16) and mobility (N = 14), and other tasks (N = 18). Five articles reported on two different tasks. Specific scanning behaviour related to task performance in search, reading, and mobility tasks. In search and reading tasks, spontaneous adaptations differed from this performance-enhancing scanning behaviour. Training could induce adaptations in scanning behaviour, enhancing performance in these two tasks. For mobility tasks, limited to no information was found on spontaneous and training-induced adaptations to scanning behaviour. Performance-enhancing scanning behaviour is mainly task-specific. Spontaneous development of such scanning behaviour is rare. Luckily, current compensatory scanning training programs can induce such scanning behaviour, which confirms that providing scanning training is important. Scanning behaviour that improves performance in people with homonymous hemianopia (HH) is task-specific. Most people with HH do not spontaneously adopt scanning behaviour that improves performance. Compensatory scanning training can induce performance-enhancing scanning behaviour.